Mengembangkan Keterampilan Berpikir Kreatif pada Mata Pelajaran SBdP Siswa Kelas V di SD Negeri Karawaci 1 - Syapitri, Gita Harnum; Azdi, M.; Suhendar, Asep (MASALIQ, 2023)
This study aims to describe the way teachers develop deep creative thinking skills SBdp learning for fifth grade students at SDN Karawaci 1. Study this is type study qualitative with approach descriptive. subject study this is a teacher and student class V SDN Karawaci 1. Engineering data collection using observation, interview, and studies documentation. Results study show that there are some students who are still not able to hone their creative thinking skills in SBdp subjects from 27 students class V. It is caused student afraid will error, less believe self and not enough understand objective learning. By because the teacher of class V gave related material with issue or problem, give chance on student for deepen topic already conveyed, pushed student for produce idea or new ideas, and push student for elaborate the idea. Whereas for develop Skills think creative students, teachers train smoothness for role active in ask as well as answer and disclose idea or idea, train flexibility for make a group in do discussion in accordance existing theme given, train novelty for generate their own different ideas in a group, and the last practice elaboration with give material or more tasks specific.